Cucurbitacin B inhibits human breast cancer cell proliferation through disruption of microtubule polymerization and nucleophosmin/B23 translocation - Duangmano Suwit; Sae-lim Phorntip; Suksamrarn Apichart; Domann Frederick E; Patmasiriwat Pimpicha (BMC, 2012)
Abstract Background Cucurbitacin B, an oxygenated tetracyclic triterpenoid compound extracted from the Thai medicinal plant Trichosanthes cucumerina L., has been reported to have several biological activities including anti-inflammatory, antimicrobial and anticancer. Cucurbitacin B is great of interest because of its biological activity. This agent inhibits growth of various types of human cancer cells lines. Methods In this study, we explored the novel molecular response of cucurbitacin B in human breast cancer cells, MCF-7 and MDA-MB-231. The growth inhibitory effect of cucurbitacin B on breast cancer cells was assessed by MTT assay. The effects of cucurbitacin B on microtubules morphological structure and tubulin polymerization were analyzed using immunofluorescence technique and tubulin polymerization assay kit, respectively. Proteomic analysis was used to identify the target-specific proteins that involved in cucurbitacin B treatment. Some of the differentially expressed genes and protein products were validated by real-time RT-PCR and western blot analysis. Cell cycle distributions and apoptosis were investigated using flow cytometry. Results Cucurbitacin B exhibited strong antiproliferative effects against breast cancer cells in a dose-dependent manner. We show that cucurbitacin B prominently alters the cytoskeletal network of breast cancer cells, inducing rapid morphologic changes and improper polymerization of the microtubule network. Moreover, the results of 2D-PAGE, real-time RT-PCR, and western blot analysis revealed that the expression of nucleophosmin/B23 and c-Myc decreased markedly after cucurbitacin B treatment. Immunofluorescence microscopy showed that cucurbitacin B induced translocation of nucleophosmin/B23 from the nucleolus to nucleoplasm. Treatment with cucurbitacin B resulted in cell cycle arrest at G2/M phase and the enhancement of apoptosis. Conclusions Our findings suggest that cucurbitacin B may inhibit the proliferation of human breast cancer cells through disruption of the microtubule network and down-regulation of c-Myc and nucleophosmin/B23 as well as the perturbation in nucleophosmin/B23 trafficking from the nucleolus to nucleoplasm, resulting in G2/M arrest.